(untitled) (Ekonomi : Jurnal Perbankan Syariah, 2025)
This study discusses the implementation of the Three Pillars of Education in the context of educational politics in Indonesia, with the main focus on understanding the factors that influence its implementation. These factors include the impact of educational political policies, government support, and internal dynamics within schools. The research method used is the analysis of secondary data obtained from academic literature and relevant policy documents. The results of the study indicate that consistent and supportive educational political policies play a significant role in shaping the strategies and operationalization of the Three Pillars in schools. Government support—particularly in terms of funding, infrastructure provision, and human resource development—greatly influences the capacity of schools, especially public schools, to implement the Three Pillars effectively. These findings provide in-depth insights into the complexity of implementing the Three Pillars and serve as a basis for formulating more effective policies to strengthen the strategic role of schools in the development of the Country region.